Pengaruh Model Pembelajaran Missouri Mathematics Project dengan Metode Talking Stick terhadap Hasil Belajar Siswa MTS Negeri Tuban - Akrom, Mochamad; Yuliastuti, Rita; Nawangsari, Tanti (Universitas Negeri Surabaya, 2020)
Â This research aimed to test the influence of the independent variable which is Missouri Mathematics Project (MMP) learning model using talking stick method against its dependent variable which is the outcome of studentsâ€™ mathematics learning, that are conducted on the second semester of 2015/2016 school year. This research used pretest-posttest design and random subject class control. The study population that was used in this research are the whole students of 7th grade of MTS Negeri Tuban that have 9 classrooms which consist of 275 students. The sample on this research is 7th-grade students in class I as experimental class, totaling 31 students that were taught by MMP learning models using talking stick method. While class H which consist of 29 students is as control class that were taught by direct instruction. The outcome of this research is some effect have shown on the students that are taught by using MMP learning models using talking stick method towards their mathematics learning outcom